The Influence of Live TikTokShop in Building Customer Trust and Customer Engagement through Perceived Value - Sidik, Tri Wahyu Fajar; Roostika, Raden Roro Ratna (MEC-J (Management and Economics Journal), 2024)
The trend of home shopping or shopping from home through online platforms such as conventional e-commerce and social commerce is currently popular. One of the social commerce that is often used by the Indonesian people is TikTokShop. The live stream feature is currently widely installed in various online media and e-commerce media, one of which is the TikTokShop platform. The fear and worry when shopping through an online platform is when what is ordered does not match what is desired. With the live stream feature, customers can see the product in real time so they can avoid their worries. This study aims to conduct an in-depth analysis of the influence of live stream marketing innovation on the TikTokShop social commerce application. A total of 210 participants received an online survey, then the results of the survey will be analyzed with descriptive statistics, using the PLS-SEM version 4.0 application, and SPSS to test quantitative data. The results of this study indicate that utilitarian value does not have a significant effect on trust in product, trust in seller, or customer engagement in live stream commerce. In contrast, hedonic value has a positive and significant effect on trust in seller and customer engagement, but does not affect trust in product. Meanwhile, trust in the product also has a positive and significant effect on trust in the seller and customer engagement. Finally, trust in the seller has a positive and significant effect on customer engagement. This study explains how the live stream feature can affect customer trust and engagement, so that it can help business actors increase their sales. This study can also be an additional reference for marketing managers and additional knowledge.